KONTRIBUSI PEMAHAMAN TEKS PROSEDUR TERHADAP KETERAMPILAN MENULIS TEKS PROSEDUR SISWA KELAS VII SMP NEGERI 10 PADANG - Guci, Khairani Ulya; Hafrison, Mhd. (Universitas Negeri Padang, 2019)
ABSTRACTÂ This article reveals the contribution of skills reading comprehension text procedure to writing skills text description grade students VII SMP Negeri Padang 10. The purpose of this research there are three. First, it describes the skills of reading comprehension text procedure grade VII SMP Negeri 10 field. Second, it describes the writing skills text procedure grade VII SMP Negeri 10 field. Third, describing the contribution of the intermediate reading comprehension text procedure against writing skills text procedure grade VII SMP Negeri 10 field. This research type is quantitative descriptive method. The design used in this research is the design contribution. This research population is grade VII SMP Negeri Padang are registered on the 12th school year 2018/2019.The sample in this research are determined by proportional random sampling of 20% of the population, 54 students. Research data is a score test results intermediate reading comprehension text procedure and score the writing skills test result text procedure. The data obtained through two types of tests objective tests to measure the skills of reading comprehension text procedure and performance tests to measure the skills of writing a text procedure. The results of the research there are three. First, the skills of reading comprehension text procedure grade VII SMP Negeri Padang 10 are on good qualifications (B) by the value of the average 80.09. Second, the skills of writing text procedure grade VII SMP Negeri Padang 10 are on good qualifications (B) with an average of 80.71. Third, there is a contribution of reading skills in the procedure of text to the skills of writing procedure texts of class grade VII SMP Negeri Padang 10 at 51,55%Â Â Kata kunci: Membaca Pemahaman, Menulis Teks Prosedur